Simultaneous catalytic oxidation of Hg0 and AsH3 over Fe–Ce co-doped TiO2 catalyst under low temperature and reducing atmosphere. Issue 6 (27th January 2023) - Yu, Huijuan; Zhang, Yingjie; Quan, Hong; Zhu, Dan; Liao, Shaohua; Gao, Cuiping; Yang, Rongbin; Zhang, Zhenyu; Ma, Qiang
Abstract : Fe5 Ce5 Ti catalytic material is reported for the removal of Hg 0 and AsH3 from yellow phosphorus flue gas by catalytic oxidation. The mechanism of the reaction is inferred from characterization analysis. Abstract : The Fe–Ce bimetal oxide-doped titanium dioxide composite was synthesized by the sol–gel method and the performance of the catalyst was investigated for the removal of Hg 0 and AsH3 from yellow phosphorus flue gas under different conditions. Brunauer–Emmett–Teller (BET) analysis, high-resolution transmission electron microscopy (HR-TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) were used to characterize the crystal structure and morphology of the structure, and the mechanisms for removing Hg 0 and AsH3 from flue gas by catalytic oxidation were deduced. The results showed that the optimal calcination temperature of the Fe5 Ce5 Ti catalyst was 500 °C, and the optimal pH of the sol was 6. Under these conditions, the penetration adsorption capacity of the Fe5 Ce5 Ti catalyst for the removal of AsH3 and Hg 0 was 385.5 mg g −1 and 2.178 mg g −1, respectively. According to characterization analysis, Fe and Ce are the main active components in the removal of Hg 0 and AsH3, and the mixed oxides of Fe and Ce have a synergistic effect on the surface of the mixed oxide-doped catalyst, which can improve the dispersion of the active component on the surface of the catalyst, and then improve the removal efficiency of Hg 0 and AsH3 .